2014
DOI: 10.1186/1476-9255-11-17
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of Staphylococcus aureus biofilm secreted products on inflammatory responses of human epithelial keratinocytes

Abstract: BackgroundChronic wounds such as diabetic foot ulcers, pressure ulcers, and venous leg ulcers contribute to a considerable amount of mortality in the U.S. annually. The inability of these wounds to heal has now been associated with the presence of microbial biofilms. The aim of this study was to determine if products secreted by S. aureus biofilms play an active role in chronic wounds by promoting inflammation, which is a hallmark of chronic wounds.MethodsIn vitro experiments were conducted to examine changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 55 publications
5
38
0
1
Order By: Relevance
“…We found an upregulation of proinflammatory cytokines IL‐1β, IL‐6, IL‐8, and TNF‐α upon live S. aureus treatment. An upregulation of gene expression of these cytokines in NHEKs was reported using S. aureus biofilm–secreted products, S. aureus biofilm–conditioned medium, or planktonic‐conditioned medium . An involvement of these cytokines in the S. aureus –induced increase in TER is also supported by the fact that the addition of IL‐1β and TNF‐α to infected keratinocytes here produced a short‐term TER‐increasing effect.…”
Section: Discussionsupporting
confidence: 72%
“…We found an upregulation of proinflammatory cytokines IL‐1β, IL‐6, IL‐8, and TNF‐α upon live S. aureus treatment. An upregulation of gene expression of these cytokines in NHEKs was reported using S. aureus biofilm–secreted products, S. aureus biofilm–conditioned medium, or planktonic‐conditioned medium . An involvement of these cytokines in the S. aureus –induced increase in TER is also supported by the fact that the addition of IL‐1β and TNF‐α to infected keratinocytes here produced a short‐term TER‐increasing effect.…”
Section: Discussionsupporting
confidence: 72%
“…). The reduction in primary HK viability , proliferation , and migration due to BCM and PCM was later confirmed by other investigators using different strains of S. aureus . BCM‐induced apoptosis was also demonstrated in another primary HK investigation and in the HaCaT cell line , which is an immortalized keratinocyte cell line.…”
Section: Epidermal Investigationssupporting
confidence: 63%
“…Using primary HK, Tankersley et al. performed a similar investigation. They examined the production of IL‐1, IL‐6, IL‐8, TNF‐α, and CXCL‐2 after both 4 and 8 h of exposure to either S. aureus BCM or PCM.…”
Section: Epidermal Investigationsmentioning
confidence: 99%
“…We also observed that the biomass attached to UV-treated titanium remained sparse, predominantly consisting of individual attached cells and small cell clusters compared to untreated surfaces that were mostly covered in maturing biofilms comprised of large colonies that appeared to be encased in matrix material. In addition to preventing host cell attachment to the implant by competing for space, biofilms have also been shown to elicit much stronger inflammatory response – an important reason for bone loss – compared to planktonic bacteria [57, 58]. Furthermore, bacteria contaminating titanium implants have been demonstrated to migrate into and infect surrounding tissues, while apparently not being cleared by macrophages [59].…”
Section: Discussionmentioning
confidence: 99%